Abnormal intrinsic functional network hubs and connectivity following peripheral visual loss because of inherited retinal degeneration. Issue 4 (6th March 2019) - Huang, Xin; Dan, Han-Dong; Zhou, Fu-Qing; Deng, Qin-Qin; Shen, Yin
Abstract : Previous neuroimaging studies have shown that the long-term effects of peripheral vision loss lead to functional and morphological reorganization in visual cortices. However, it has not been determined whether whole-brain functional network centrality changes occur during peripheral vision loss. This study aimed to investigate functional network centrality and connectivity changes in individuals with peripheral vision loss because of retinitis pigmentosa (RP) by using voxel-wise degree centrality (DC) and seed-based resting-state functional connectivity (rsFC) methods. In total, 30 RP patients (18 men and 12 women, mean age: 38.77±14.44 years) and 30 healthy controls (HCs) (18 men and 12 women, mean age: 34.57±10.70 years) matched for age, sex, cognition, education, and visual expertise underwent resting-state magnetic resonance imaging scans. Graph theory-based network analysis was carried out to investigate DC between the two groups. A seed-based rsFC analysis was then carried out to further reveal the abnormal functional connectivity of the altered DC brain region. Pearson's correlation was used to analyze the relationships of DC and rsFC index with the clinical variables in RP patients: visual function (best-corrected visual acuity and visual field, VF) and optical coherence tomography testing (mean retinal nerve fiber layer). Compared with HCs, RP patients had significantly lower DC values in the bilateral cuneus/calcarine/precuneus (CUN/CAL/PreCUN) [Brodmann's area (BA) 17/18/19/30/31]. In addition, RP patients showed decreased rsFC index, relative to that of HCs, from bilateral CUN/CAL/PreCUN to bilateral lingual/cuneus/calcarine (LIG/CUN/CAL) (BA 18/19/30) and the bilateral postcentral gyrus/superior parietal lobule (BA 3/5/7/40). In contrast, RP patients showed increased rsFC index, relative to that of HCs, from bilateral CUN/CAL/PreCUN to bilateral thalamus/caudate (voxel-level P <0.01; Gaussian random-field correction, cluster-level P <0.05). Moreover, the course of RP showed a negative correlation with the mean DC values of the bilateral CUN/CAL/PreCUN ( r =−0.480; P =0.007) and the mean FC values of the bilateral LIG/CUN/CAL ( r =−0.484; P =0.007); the mean DC values of the bilateral CUN/CAL/PreCUN in RP showed a negative correlation with the right eye VF ( r =−0.411; P =0.024) and left eye VF ( r =−0.426; P =0.019). Our results showed that RP patients showed abnormal function network hubs in various brain regions related to visual, thalamocortical, and sensorimotor networks; these might reflect impaired top–down modulations, visual imagery, and visuomotor coordination in RP patients. Moreover, the DC index can be used as a biomarker to indicate the severity of visual loss in RP patients.